Diagnostic power of the noninvasive condom catheter method in patients eligible for transurethral resection of the prostate. Issue 4 (11th June 2013) - van Mastrigt, Ron; de Zeeuw, Sandra; Boevé, Egbert R.; Groen, Jan
Abstract Aims The aim of this study was to determine the accuracy of the non‐invasive condom catheter method for diagnosing B(ladder) O(utlet) O(bstruction) in patients eligible for T(rans)U(rethral) R(esection) of the P(rostate). Methods A group of 71 patients eligible for TURP on clinical grounds were invasively and non‐invasively studied. On the basis of invasive pressure‐flow studies they were stratified into obstructed, equivocal or unobstructed, according to the International Continence Society standard. Subsequently they were diagnosed non‐invasively on the basis of a free flowrate measurement, or on the basis of the free flowrate measurement plus the isovolumetric bladder pressure measured with the condom catheter method. R(eceiver) O(perating) C(haracteristic)s were calculated. Results The A(rea) U(nder) the (RO)C for discriminating unobstructed/equivocal patients from obstructed patients was 0.68 in our population. This improved to 0.84 for the 50 patients in whom the isovolumetric bladder pressure was not underestimated by the non‐invasive method. Conclusions In our population of TURP patients, the low flowrates affected the accuracy of the condom method to a degree that it did not perform better than a free flowrate measurement, which performed remarkably well. By excluding measurements in which the condom pressure underestimated the isovolumetric bladder pressure this method may contribute to a more accurate, patient friendly diagnosis of BOO in these patients. In the present study this exclusion was done by comparison with an invasive pressure measurement. A practical non‐invasive test would necessitate a non‐invasive exclusion criterion, which might be based on the risetime of the condom pressure. Neurourol. Urodynam. 33:408–413, 2014. © 2013 Wiley Periodicals, Inc.